Disinfection of Water by Chlorine, Peracetic Acid, Ultraviolet and Solar Radiations: A Review - Paggiaro, Juliana; Souza, Aline Karla Nolberto de; Ribeiro Bihain, Murielly Fernanda; Santos Pereira, Anna Karla dos; Cavallini, Grasiele Soares; Pereira, Douglas Henrique (Fine Chemical Engineering, 2024)
Disinfection is an essential step during water treatment to ensure the microbiological safety of water for human consumption, and over time, it has been improved and better understood. In this context, this review provides a compilation of information, new insights, and perspectives on the main microorganisms present in supply water, their basic structures, and mechanisms of disinfection via chlorine, peracetic acid (PAA), ultraviolet (UV) radiation and solar disinfection (SODIS). Chlorine is the most common chemical disinfectant, however, there is the formation of toxic by-products, which has stimulated the use of non-chlorinated disinfection methods, such as PAA, UV and SODIS. The main advantages of PAA reported in the literature are its high disinfecting power, the non-formation of toxic/carcinogenic by-products, its ability to generate radicals, such as CH3C(O)O●, HO● and HOO● with or without the use of electromagnetic radiation or thermal energy. The generation of radicals is one of the most used mechanisms to explain the oxidation process during disinfection, which, also prompted studies to use radiation for catalyzing the formation of these radicals. Consequently, physical disinfection processes, such as UV irradiation and SODIS have received significant attention because, in addition to having the ability to damage the RNA (Ribonucleic Acid) and DNA (Deoxyribonucleic Acid) of microorganisms causing their inactivation, these processes also promote the formation of radicals through reactive species that are ubiquitous in natural water. Therefore, the review will be important for studies focused on the process of water disinfection by advanced oxidized processes, especially those that use PAA combined with UV or SODIS.